PENERAPAN MODEL PROBLEM BASED LEARNING DENGAN APLIKASI SI-BAD TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SD - Permadani, Rohani Anggita; Ermawati, Diana; Amaliyah, Fitriyah (MES: Journal of Mathematics Education and Science, 2025)
The purpose of this study was to determine the effectiveness of the SI-BAD application-assisted problem-based learning model in improving students' mathematical problem-solving skills. This study was a pre-experimental quantitative study with a one-group pretest-posttest design conducted in class V of SDN Mangunrejo 1 with a population of 19 students. The sampling technique used in this study was saturated sampling. The data collection techniques used were tests and documentation. The data analysis techniques used were the paired sample t-test and the N-Gain test. The results of the study showed that the SI-BAD application-assisted problem-based learning model was effective and that there was an increase in students' mathematical problem-solving skills after using this model. The results of the paired sample t-test showed that the use of the SI-BAD application-assisted problem-based learning model was effective in improving students' mathematical problem-solving skills. It was found that the percentage of improvement in students' abilities was 60.02%, which is considered quite effective.